2020
DOI: 10.1103/physreve.101.012407
|View full text |Cite
|
Sign up to set email alerts
|

Active modulation of surfactant-driven flow instabilities by swarming bacteria

Abstract: Models based on surfactant driven instabilities have been employed to describe pattern formation by swarming bacteria. However, by definition, such models cannot account for the effect of bacterial sensing and decision making. Here we present a more complete model for bacterial pattern formation which accounts for these effects by coupling active bacterial motility to the passive fluid dynamics. We experimentally identify behaviours which cannot be captured by previous models based on passive population disper… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 26 publications
(12 reference statements)
0
5
0
Order By: Relevance
“…Modification of this model to incorporate chemosensing and motility showed that swarm tendrils could detect and be repelled by antibiotics. 124 While these reports have demonstrated that swarm tendrils and the advancement of the swarm front can be explained by Marangoni flows, it is unclear whether this is the primary mechanism that drives swarm expansion or tendril formation.…”
Section: Role Of Fluid Mechanics In Swarm Expansion and Tendril Forma...mentioning
confidence: 99%
“…Modification of this model to incorporate chemosensing and motility showed that swarm tendrils could detect and be repelled by antibiotics. 124 While these reports have demonstrated that swarm tendrils and the advancement of the swarm front can be explained by Marangoni flows, it is unclear whether this is the primary mechanism that drives swarm expansion or tendril formation.…”
Section: Role Of Fluid Mechanics In Swarm Expansion and Tendril Forma...mentioning
confidence: 99%
“…Fauvart et al (2012) showed through both theory and experiments the swarming behaviour of Pseudomonas aeruginosa driven by surface forces. The recent work by Kotian et al (2020) includes the effects of van der Waals forces, in addition to solving an evolution equation for the swimmer density field and accounting for its effects on the surfactant concentration field. Kotian et al (2020) wrote down a free energy functional pertaining to the long-range van der Waals forces and the surface forces generated by the Marangoni stresses in the system.…”
Section: Introductionmentioning
confidence: 99%
“…The recent work by Kotian et al (2020) includes the effects of van der Waals forces, in addition to solving an evolution equation for the swimmer density field and accounting for its effects on the surfactant concentration field. Kotian et al (2020) wrote down a free energy functional pertaining to the long-range van der Waals forces and the surface forces generated by the Marangoni stresses in the system. Subsequent minimization of the free energy functional, to generate the governing equations of the system, has also been done by Trinschek et al (2017), with an added contribution to the free energy arising from the mixing of solute and solvent phases.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations